First Report of Response to Tarlatamab in a Patient With DLL3-Positive Pulmonary Carcinoid: Case Report - Alissa J. Cooper, MD; Natasha Rekhtman, MD, PhD; Marina K. Baine, MD, PhD; Marie C. Thomas, DNP, FNP-C; Alia C. Lynch, PharmD, BCOP; Ryan D. Gentzler, MD, MS (JTO Clinical and Research Reports)
Tarlatamab, a DLL3-targeting bispecific T-cell engager, has rapidly assumed the role of a new standard of care in the later-line treatment of extensive-stage SCLC. Little is known about the efficacy of tarlatamab in other histologies such as DLL3-expressing metastatic pulmonary carcinoid tumor, a clinical entity without many approved management options. Here, we report the case of a patient with metastatic atypical carcinoid tumor which had progressed on multiple previous therapies. Her tumor strongly expressed DLL3 protein and had clinical response to tarlatamab therapy. This case indicates that this novel therapy may be an efficacious option in other pulmonary neuroendocrine cancers.